Promotion, Scaling, and Market Positoning of Specialty Rice in Odisha - Nayak, Swati; Hossain, Sk Mosharaf (International Rice Resesrch Institute, 2025)
The Specialty Rice Initiative was implemented to enhance farmer income, market integration, and varietal diversification through the promotion of high-value specialty rice varieties across selected production clusters. The program focused on aligning breeding outputs with consumer and market demand by integrating improved specialty rice varieties, quality seed availability, scientific crop management, and organized market linkages. On-farm demonstrations and varietal evaluations revealed the superior performance of selected specialty rice types in terms of yield stability, grain quality, and price realization compared to conventional varieties. Strengthening of local seed systems, including farmer-led seed production and institutional support, ensured timely access to quality seed and improved varietal adoption. The initiative also emphasized capacity building of farmers, extension personnel, and value-chain actors to improve post-harvest handling, quality assurance, and traceability. By fostering collaboration among research institutions, extension agencies, private actors, and farmer organizations, the program demonstrated a scalable pathway for integrating specialty rice into mainstream production systems, thereby contributing to income diversification, value addition, and sustainable growth of the rice sector.